Progress in computer vision and image analysis - Bunke, Horst (Series in machine perception and artificial intelligence ;, 2010)
This book is a collection of scientific papers published during the last five years, showing a broad spectrum of actual research topics and techniques used to solve challenging problems in the areas of computer vision and image analysis. The book will appeal to researchers, technicians and graduate students.